Parametric optimization of the production of carbon nanotube yarn from CVD reactor - Bodiba, Veronica (My University, 2020)
Carbon nanotubes (CNTs) have attracted research efforts due to their excellent properties which include; high tensile strength, good thermal and electrical conductivities. To utilize their good properties, CNTs can be further made into strong pure CNT yarns by spinning them. However, the production of macroscale carbon nanotube (CNT) yarns that has similar or excellent properties as microscale CNTs is still a problem. Thus the produced CNT yarns usually have low quality due to defects formed during the production process. This is because CNT bundles tend to slide in yarn microstructures, thus making it difficult to transfer individual CNT properties into spun yarn structure. Furthermore, the amount of CNT yarn produced using CVD method is very small. Therefore, this research will focus on parametric optimization of production parameters for achieving high CNT yarn yield and enhancing CNT yarn properties. The interested parameters include; the reaction temperature, flow rate of carbon precursor (methane) and the state of the catalyst.Hence it was necessary to optimize the CNT yarn production using CVD reactor with the aim of enhancing the yield and quality. Single-walled carbon nanotubes (SWCNTs) have a higher electrical conductivity as compared to multi-walled carbon nanotubes (MWCNTs) thus the production of SWCNTs is desired. Methane gas was chosen as the carbon precursor for this study because literature states that saturated hydrocarbons produce large amounts of SWCNTs than unsaturated hydrocarbons. Moreover, methane is a natural gas and it is available everywhere in the world, therefore the production process will be very affordable and the usage of methane might decrease global warming. Thus methane gas was used to help obtain more single-walled carbon nanotubes. The parametric variables including reactor temperature, flow rate of carbon precursor and the state of catalyst were manipulated into improving the yield and quality of CNT yarns. Individual CNTs have excellent properties; however it is difficult to produce CNT yarns with similar properties as individual CNTs. CNT yarns appear to be more of interest to researchers because of their versatility in real life application. With that said; the study contained in this dissertation investigated the parametric optimization for the production of CNT yarn using CVD method. v Carbon nanotube yarns are nano-scale filamentary composites made up of individual CNTs aligned in cross-section that follows helical paths at different angles about the yarn axis. Carbon nanotube yarn properties increases with increasing length and decreasing diameter. Other factors that affect the electrical and mechanical properties of CNT yarns are; densification, water evaporation and CNT orientation. Theory states that mechanical strength is directly proportional to CNT yarn length and is inversely proportional to the CNT yarn diameter. Furthermore, CNT yarn has got excellent mechanical properties and good electrical conductivity too. The objective of this research was to produce and characterize CNTs and CNT yarn from CVD reactor; and to investigate the effect of operating parameters (reactor temperature, methane flow rate and the effect of dissolving catalyst in liquid hydrocarbons). The production of the CNT yarn was carried out using CVD method in the following four steps: (i) The production of CNTs, (ii) Conversion of CNTs to CNT yarn and (iii) Characterization of the CNT yarn. The Response Surface Methodology (RSM) was used to develop the empirical equation for predicting the experimental responses and this model was justified using experimental data. The experiments were carried out using a vertical CVD reactor with methane as a precursor and Ferrocene as a catalyst. From the results obtained in this study show that CNT yield is higher when cyclopentane is used to dissolve Ferrocene as compared to the production were solid Ferrocene was used. SEM images have shown better CNT morphology when catalyst state was changed to liquid by dissolving ferrocene in cyclopentane. Moreover, the CNTs produced with liquid state catalyst were more pronounced, free of impurities, more aligned and longer compared to the CNTs produced with solid Ferrocene. The optimal CNTs achieved were produced at 1000ºC using liquid catalyst. The amount of the sample obtained at the optimal conditions was 165 mg and the electical conductivity and the ID/IG ratio were 0.2388 mA and 0.16, respectively. The CNT yarn was then produced with Ferrocene dissolved in cyclopentane since the best results from CNTs production were obtained when using liquid catalyst. CNT yarns were produced at methane flow rate of 160 ml/min and 150 ml/min while varying temperature between 900℃−100℃. CNT yarn yield improved at higher methane flowrate and increased with increasing temperature. The results from SEM images showed evidence of impurities from the catalyst. The sample’s ID/IG ratios and electrical conductivity improved with the increasing reaction temperature and worsened with increasing methane flow rate. After completing the optimization study, optimal CNT yarn production was achieved at 967ºC reaction temperature with 150 ml/min methane flow rate. The yield and the electrical conductivity of the CNT yarn synthesized at optimal conditions were found to be 24.72 mg and 0.217 mA, respectively.
A thesis submitted to School of Chemical and Metallurgical Engineering, Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, South Africa